The manipulation of task constraints and the effect on creative performance of youth soccer players - Tom De Joode (Bern Open Publishing, 2023)
Creativity is a popular topic that has been increasingly researched over the years. Recently, creativity is suggested as a relational concept (Zahno & Hossner, 2020). This conceptualization implies that creativity is not solely an individual ability. By contrast, creative actions emerge in the athlete's search to adapt to task and environmental constraints (Orth et al., 2017; Withagen & van der Kamp, 2018). Manipulating task constraints that serve to increase variability might, therefore, evoke creative actions. Such manipulations in soccer are often conducted in training situations with small sided games. This was recently shown with a numerical assessment of creative actions comparing small sided soccer games (SSGs) with 11v11 matches in elite adult soccer players (Caso & van der Kamp, 2020). They found that players performed more actions, a broader action repertoire and more creative actions in smaller formats (5v5, 6v6 and 7v7) than in an 11v11 format. The purely quantitative method of Caso & van der Kamp (2020), however, uses an arbitrarily 5% benchmark for originality. More importantly, although subjective, the coaches opinions are not meaningless and should not be neglected. Our research examined whether the latter task manipulation also increased the action repertoire and creative performance of elite youth soccer players (O11-O13). A numerical method was introduced, assessing creative performances as a frequency of the action types emerging in an environment. A notational video-analysis identified all (not-) functional actions. Next, a threshold defined whether the action was original. This threshold has been determined with expert coaches ranking action types following the procedure of the consensual assessment technique (CAT; Amabile, 1996). If the action was both original and functional, then it was defined a creative action. The data consisted of 293 minutes small sided game (4v4) and 263 minutes regular sided game (11v11). Results indicated that small sided games hold relative more actions, more functional action and more creative actions compared with regular sided games. This is in line with previous studies, that small sided games induce more variation of actions which increase the possible emergence of creative actions (Orth et al., 2017). References Amabile, T. M., Amabile, T. M., Collins, M. A., Conti, R., Phillips, E., Picariello, M., Ruscio, J., & Whitney, D. (1996). Creativity in Context: Update to The Social Psychology of Creativity (1st ed.). Routledge. Caso, S., & van der Kamp, J. (2020). Variability and creativity in small-sided conditioned games among elite soccer players. Psychology of Sport and Exercise, 48, Article 101645. https://doi.org/10.1016/j.psychsport.2019.101645 Orth, D., van der Kamp, J., Memmert, D., & Savelsbergh, G. J. P. (2017). Creative motor actions as emerging from movement variability. Frontiers in Psychology, 8, Article 1903. https://doi.org/10.3389/fpsyg.2017.01903 Withagen, R., & van der Kamp, J. (2018). An ecological approach to creativity in making. New Ideas in Psychology,49, 1-6. https://doi.org/10.1016/j.newideapsych.2017.11.002 Zahno, S., & Hossner, E.-J. (2020). On the issue of ceveloping creative players in team sports: A systematic review and critique from a functional perspective. Frontiers in Psychology, 11, Article 575475. https://doi.org/10.3389/fpsyg.2020.575475